The British publishing industry in the Nineteenth Century.
1 online resource (xxvi, 386 pages)
Keywords: This volume assembles documents that illustrate the changing relations between authors and publishers in the nineteenth century, and the impact of copyright reform on publishing practices. The enormous expansion in the scale and variety of the marketplace for print after 1815 provided new opportunities for authors and prompted debates over intellectual property and the working relations between authors and publishers. The volume documents the impact of these changes on the publishing industry and its markets, focusing on key moments such as the emergence of the professional literary agent in the late 1870s and the formation of the Incorporated Society of Authors in 1883. It also includes key contemporary material related to copyright and intellectual property, which were major battle grounds affecting nineteenth-century textual circulation, author/publisher relations, financial sustainability, competitiveness in international markets, and industrial relations. The British publishing industry⁰́₉s attempts to control piracy and unrestricted circulation of their titles in the US and elsewhere found expression in a number of pressure campaigns, formal government commissions, legal acts, and contributions to public debate through journal articles, pamphlets, speeches, and newspaper accounts, of which a representative selection are featured in this volume.